2018
DOI: 10.3892/mmr.2018.9013
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol induces hemangioma endothelial cell apoptosis via a p53‑BAX mediated pathway

Abstract: The use of propranolol for the treatment of infantile hemangioma (IH) has been widely investigated in recent years. However, the underlying therapeutic mechanism of propranolol for the treatment of IH remains poorly understood. The aim of the present study was to investigate the expression of proteins regulated by cellular tumor antigen p53 (p53) in associated apoptosis pathways in IH endothelial cells (HemECs) treated with propranolol. Furthermore, the present study aimed to investigate the exact apoptotic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…According to recent studies focusing on the potential mechanisms of different anti-hemangioma drugs, propranolol and other beta-blockers mainly exert their effects via targeting hemangioma endothelial cells and hemangioma pericytes (30). Bischoff et al proposed that propranolol could suppress the development of hemangiomas through increasing the contractility of hemangioma pericytes (31), and several other studies reported that propranolol could inhibit the growth of hemangiomas through modulating cellular functions of hemangioma endothelial cells (3234). Although no significant differences in the therapeutic efficacy of propranolol group and timolol group in our study were observed, we hypothesized that systemic propranolol and local timolol might individually exerted their effects partly via targeting different cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies focusing on the potential mechanisms of different anti-hemangioma drugs, propranolol and other beta-blockers mainly exert their effects via targeting hemangioma endothelial cells and hemangioma pericytes (30). Bischoff et al proposed that propranolol could suppress the development of hemangiomas through increasing the contractility of hemangioma pericytes (31), and several other studies reported that propranolol could inhibit the growth of hemangiomas through modulating cellular functions of hemangioma endothelial cells (3234). Although no significant differences in the therapeutic efficacy of propranolol group and timolol group in our study were observed, we hypothesized that systemic propranolol and local timolol might individually exerted their effects partly via targeting different cells.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting cell cycle arrest and apoptosis are the main mechanisms of action of drugs for the treatment of IH ( Chen et al, 2019 ). In particular, p53 signaling pathway mediated apoptosis ( Yao et al, 2018 ). The mammalian rapamycin complex (mTOR), which converts signals in the extracellular environment, such as glucose and growth factors, into corresponding changes in basic intracellular processes, including proliferation ( Laplante and Sabatini, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that CCNB1 silencing suppressed the expression of CCNB1 and CDK1 but increased the expression of Bax, caspase 3, caspase 9, p53 and p21. Bax has been reported to be directly activated by p53 in the absence of other proteins to permeabilize mitochondria and initiate the apoptotic program[ 46 - 48 ]. Moreover, p53-induced apoptosis involves triggering the caspase-9 initiator and its downstream caspase-3 executioner.…”
Section: Discussionmentioning
confidence: 99%